ANALISIS NORMALISASI HUBUNGAN DIPLOMATIK ANTARA MAROKO DAN ISRAEL PADA TAHUN 2020 - Diffa Anindra Pratama; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research aims to analyze the reasons why Morocco normalized its diplomatic relations with Israel in 2020. The normalization agreement brokered by the United States has given Morocco strategic advantages in geopolitical, military, economic and other aspects. On the other hand, Morocco's move has become a controversial topic, because it is related to the historical conflict and political dynamics of Arab countries that oppose Israel. Morocco's normalization agreement with Israel calls for the two countries to officially open access to contacts and resume diplomatic relations This research uses an explanatory qualitative method, with data collection techniques through literature studies sourced from several books, journals, reports, websites and theses. This research uses a behavioral perspective and decision making theory. The results of this research explain that the normalization agreement between Morocco and Israel is Morocco's rational policy to achieve its national interests, especially regarding the Western Sahara issue. The agreement is a form of response to potential security threats from the Polisario Front which is supported by Algeria and Iran. The normalization agreement with Israel, provides Morocco with diplomatic support for its integrity in Western Sahara and opens access to exploit Israel's military advantages, and other sectors. However, the normalization agreement has increased regional instability, especially diplomatic tensions between Morocco and Algeria. Keywords: Normalization, Polisario Front, Foreign Policy, Western Sahara